Architectural framework for a United Blockchain Interaction Library - Dobrianskyi, B.I.; Stetsenko, I.V. (PROBLEMS IN PROGRAMMING, 2024)
This research addresses the challenges posed by the fragmented nature of blockchain development tools, presenting a comprehensive exploration of the imperative need for a unified architecture. In response to the growing diversity of blockchain networks, a solution in the form of a unified library based on a versatile and interoperable interface that streamlines interactions across various blockchains is proposed. The current state of blockchain development tools, an overview of existing solutions, formulation of design principles, and functions of proposed unified library are provided. By mitigating the complexities associated with disparate tools, the research aims to enhance the accessibility and efficiency of blockchain development, encouraging collaboration and innovation within the blockchain community.Problems in programming 2024; 1: 86-95